Collaborative activity for teaching-learning about Basic Health Care (Research, Society and Development, 2022)
Objective: To report the experience of collaborative activity for teaching-learning about Primary Health Care. Method: Descriptive experience report carried out using the Team-Based Learning method and analyzed by the Activity Theory. It was carried out between January and June 2021 through the Curricular Activity of Integral Attention to Adult and Elderly Health at the Faculty of Nursing of the Federal University of Pará during the remote emergency period. Result: Collaborative competences were developed from teaching-learning stages on aspects related to the infrastructure of services, biosecurity, human resources and instruments to support practical skills for professional training. Final Considerations: The use of digital resources for collaborative learning enabled individual, paired, dynamic and integrated engagement. The experience contributed to learning about the organization of the Primary Health Care work process and to the discussion on the subject from the perspective of the Unified Health System.